Strengthening your hip muscles - Some exercises may be better than others (Journal of Orthopaedic & Sports Physical Therapy, 2013)
Weak hip muscles lead to poor hip motion, and poor hip motion can cause knee, hip, and back pain. By exercising to strengthen the hip muscles that control how your hip moves, you can reduce your pain in these parts of your body. The 2 key muscles to include in your exercise program are the gluteus maximus (the chief muscle on the back of your hip—your buttocks) and the gluteus medius (the main muscle on the side of your hip). However, it is often difficult to strengthen these muscles without also strengthening a muscle called the tensor fascia lata, which is located toward the front of the hip. Too much activation of that muscle may create unwanted hip motion that may worsen knee, hip, or back pain. A study published in the February 2013 issue of JOSPT provides information intended to help physical therapists and their patients select exercises that target the buttock muscles without causing other unwanted muscle actions.